2012
DOI: 10.1021/jp212211d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Cationic Pt Active for Water–Gas Shift Reaction: Pt-Doped BaCeO3 Perovskite

Abstract: Precious metal incorporated into stable lattices like perovskites can be envisaged as an alternative catalysts to address deactivation problems. Here we report the barium cerate perovskite doped with varying amounts of Pt as catalysts for the water−gas shift reaction whereby ionic Pt is evidenced to be active. It is found that maximum CO conversion occurs above 325 °C and increases more than 2-fold after the first cycle. XPS analysis shows that after the first cycle, more ionic Pt species are present on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…found a maximum CO conversion at 350 ºC and observed that the oxygen vacancies population of the system increase with the Pt substitution. Similar results were reported by Rajesh et al[75] who investigated the doping of BaCeO 3 perovskite with different amounts of Pt for the WGS reaction and they found that ionic Pt species are stabilized in lattice points of the BaCeO 3 structure increasing the oxygen vacancies of the material as increasing the Pt incorporation.From here, BaCeO 3 was proposed to be an ideal perovskite lattice to stabilize ionic Pt, maintaining it not only active but also avoiding its sintering under WGS conditions. The same authors investigated the role of oxygen vacancies in WGS reaction on BaCeO 3 perovskite co-doped with platinum and yttrium[76], concluding that the controlled addition of yttrium allows to tailor the oxygen vacancies concentration in the material, as a consequence of the Y(III) to Ce(IV) substitution.Structural and activity studies reveal that the compound with a 6% Y in its composition has the most symmetric B site coordination environment and exhibits the highest WGS activity(Figure 4).…”
supporting
confidence: 87%
“…found a maximum CO conversion at 350 ºC and observed that the oxygen vacancies population of the system increase with the Pt substitution. Similar results were reported by Rajesh et al[75] who investigated the doping of BaCeO 3 perovskite with different amounts of Pt for the WGS reaction and they found that ionic Pt species are stabilized in lattice points of the BaCeO 3 structure increasing the oxygen vacancies of the material as increasing the Pt incorporation.From here, BaCeO 3 was proposed to be an ideal perovskite lattice to stabilize ionic Pt, maintaining it not only active but also avoiding its sintering under WGS conditions. The same authors investigated the role of oxygen vacancies in WGS reaction on BaCeO 3 perovskite co-doped with platinum and yttrium[76], concluding that the controlled addition of yttrium allows to tailor the oxygen vacancies concentration in the material, as a consequence of the Y(III) to Ce(IV) substitution.Structural and activity studies reveal that the compound with a 6% Y in its composition has the most symmetric B site coordination environment and exhibits the highest WGS activity(Figure 4).…”
supporting
confidence: 87%
“…However, v′ and u′ features are characteristic of Ce 3+ oxidation state at 885.5 and 904.2 eV, and corresponds to the Ce (III) 3d 9 4f 2 -O 2p 5 configuration. 66,67 Interestingly, thin film with 50% Ce-content shows considerable broadening of the peak at 883.4 eV (feature v for Ce(IV) 3d 9 4f 1 -O 2p 5 configuration) in the XPS than other Ce compositions. This broadening is attributed to the presence of Ce 3+ at BE 885.5 eV (v′) and its corresponding 3d 3/2 component at 904.0 eV (u′).…”
Section: Hrtem Analysismentioning
confidence: 98%
“…X‐ray photoelectron spectroscopy (XPS) analysis of MCZ thin films was performed to explore the electronic structure aspects, and the results are shown in Figure for Ce 3d, Zr 4d, and Mn 2p core levels. Ce 3d spectra show two sets of spin–orbit multiplets and associated satellite features (Figure a) . Multiplets appear at 882.5 (v), 888.6 (v′′) and 898.3 eV (v′′′) binding energy (BE) and correspond to the Ce 4+ 3d 5/2 level; similarly, peaks at 901.1 eV (u), 907.6 eV (u′′) and 916.7 eV (u′′′) correspond to the Ce 4+ 3d 3/2 core level of ceria.…”
Section: Resultsmentioning
confidence: 95%